The Household Budget Survey in Western Europe, 1795-1965 - Ian Gazeley; Rose Holmes; Andrew T. Newell (Institute of Labor Economics (IZA), 2018)
We trace the development of the household expenditure survey from its conception during the Napoleonic Wars until the 1960s. We have compiled the first historical bibliography of household budget surveys in Western Europe and, using the surveys themselves as source material, have traced the development of their practice and methodology. First developed by private and academic researchers, and subsequently co-opted by governments, the surveys used the domestic consumption of working households to draw conclusions about the condition of labour. Their methodology evolved through international co-operation by researchers, and with informing the labour requirements of international trade as a priority. We argue that international networks and trans-national political structures exerted a strong influence on the development of surveys over time.
Keywords: N33; N34; O15; 330; budget studies; household expenditure surveys; living standards; cost of living inequality; working households; Europe; 20th century